Tumor-derived cytokine enhances bitter sensing through remote control of bitter taste neurons via the Upd3/Spz5/Toll-6 axis in Drosophila - Benjiang Qiao; Lingzhi Wu; Limin Chen; Jinyan Huang; Pumin Zhang; Qiaoran Li (Proceedings of the National Academy of Sciences, 2026)
The sense of taste is essential as it governs appetite and the feeding process. However, it is largely unknown whether and how tumors in a host communicate with peripheral taste sensing. Using the well-established yki S168A tumor models in Drosophila melanogaster , we found that flies carrying brain or gut tumors exhibit enhanced avoidance of bitter compounds such as caffeine but showed no avoidance of sucrose, and the degree of the avoidance was correlated with severity of the tumor phenotype. Through RNAi screening of upregulated cytokines secreted by malignant tumors, we identified Upd3 as a key factor in this process. Tumor-derived Upd3 promotes systematic increase of Spz5 expression, a fly neurotrophin, which in turn activates the Toll-6 receptor in peripheral bitter sensing neurons, leading to upregulation of the bitter-sensing receptor Gr66a. In vivo Ca 2+ imaging demonstrated heightened responses to caffeine by Gr66a + neurons in tumor-bearing flies. Interestingly, a similar phenomenon was observed in murine tumor models, where tumors also caused behavioral hypersensitivity to bitter tastants. Our findings reveal how tumors affect animals’ feeding behavior as well as the underlying mechanism. Our findings also suggest that such tumor-induced behavioral alterations are likely conserved across species.